Photocatalytic decomposition of rhodamine-b using scandium and silver-modified TiO2 powders - Silva, Douglas Washington da; Manfroi, Daniela Cristina; Teixeira, Guilhermina Ferreira; Perazolli, Leinig Antonio; Cavalheiro, Alberto Adriano; Zaghete, Maria Aparecida [UNESP] (Trans Tech Publications, 2014)
Semiconductor-mediated photocatalytic oxidation is an interesting method for water decontamination and a specially modified TiO2 is said to be a promising material. This study verified that the synthesis of 1wt%Ag modified-Sc0.01Ti0.99O1.995 powder samples prepared by Polymeric Precursor Method is capable of forming a mixture of anatase-rutile phase with high photocatalytic performance. This kind of material is found to have a lower bandgap compared to the TiO2-anatase commercial powders, which can be associated to an innovative hybrid modification. The simultaneous insertion of scandium in order to generate a p-type semiconductor and a metallic silver nanophase acting as an electron trapper demonstrated being capable of enhancing the degradation of rhodamine B compared to the commercial TiO2. In spite of the different thermal treatments or phase amounts, the hybrid modified powder samples showed higher photocatalytic activity than the commercial ones.
Keywords: Photocatalyst; Polymeric precursor; Scandium; Silver; Titanium dioxide